Modulation of Dental Pulp Stem Cell Odontogenesis in a Tunable PEG-Fibrinogen Hydrogel System - Qiqi Lu; Mirali Pandya; Abdul Jalil Rufaihah; Vinicius Rosa; Huei Jinn Tong; Dror Seliktar; Wei Seong Toh (Hindawi Limited, 2015)
Injectable hydrogels have the great potential for clinical translation of dental pulp regeneration. A recently developed PEG-fibrinogen (PF) hydrogel, which comprises a bioactive fibrinogen backbone conjugated to polyethylene glycol (PEG) side chains, can be cross-linked after injection by photopolymerization. The objective of this study was to investigate the use of this hydrogel, which allows tuning of its mechanical properties, as a scaffold for dental pulp tissue engineering. The cross-linking degree of PF hydrogels could be controlled by varying the amounts of PEG-diacrylate (PEG-DA) cross-linker. PF hydrogels are generally cytocompatible with the encapsulated dental pulp stem cells (DPSCs), yielding >85% cell viability in all hydrogels. It was found that the cell morphology of encapsulated DPSCs, odontogenic gene expression, and mineralization were strongly modulated by the hydrogel cross-linking degree and matrix stiffness. Notably, DPSCs cultured within the highest cross-linked hydrogel remained mostly rounded in aggregates and demonstrated the greatest enhancement in odontogenic gene expression. Consistently, the highest degree of mineralization was observed in the highest cross-linked hydrogel. Collectively, our results indicate that PF hydrogels can be used as a scaffold for DPSCs and offers the possibility of influencing DPSCs in ways that may be beneficial for applications in regenerative endodontics.